Macroscópia do encéfalo de catetos (Pecari tajacu, Linnaeus, 1758) - Saraiva, Júlio César dos Reis (Brasil, 2017)
The collared peccary (Pecari tajacu), a small-sized, omnivorous and diurnal animal, lives in groups of up to 20 animals in several areas of Brazil, the Brazilian northeast included. It is easily adapted to captive breeding and stands out in relation to cattle as an alternative protein source for human consumption, in addition to other commercial applications, posing less damage to the environment. Because there is a scarcity of studies addressing this animal, this work aimed to perform craniometry and morphometry of its cranium, as well as to describe the morphology of the encephalon and its arterial vascularization, in ventral view. We used 14 animals that died of natural causes. These had both their carotid arteries cannulated and fixation in 10% formaldehyde was then performed. From that total, ten animals were injected with latex solution, duly stained, in order to make the blood vessels evident. The skin, as well as the musculature, were rebounded. Craniometric measurements were performed. Subsequently, the encephalons were removed from the crania for measurement, dissection and description. Photographs were taken for demonstration of the structures and, after collection, the database was assembled. In the statistical analysis of the metric data, unpaired Student's t-test and Pearson’s correlation study were conducted. Thus, a significant difference was observed between the male and female collared peccaries, with regard to the Total Head Length, as well as to the face length, the cranium width, face width, and right cerebral hemisphere length, always with higher values for males. In females, the left cerebral hemisphere is wider than the right one. There was a positive correlation between the variable total head length and the right cerebral hemisphere width, in both males and females. The brain-to-body weight ratio of the collared peccaries was, on average, 0.42%. This is a gyrencephalic animal with a developed neocortex, although without evidence of sulci and gyri symmetry between the right and left cerebral hemispheres, nor between the different specimens. The arterial vascularization of the base of the encephalon is presented as a closed circuit, which is dependent on the carotid artery of the encephalon, both the antimeres, and the basilar artery, in all the analyzed specimens. The middle cerebral arteries ranged from one to three vessels, originating from the rostral branch of the cerebral carotid artery. The basilar artery results from the confluence of the vertebral arteries of both the antimeres and the ventral spinal artery. This species tends to fit into type II, of De Vriese's classification
Macroscopy of the encephalon of collared peccaries (Pecari tajacu, Linnaeus, 1758)
Keywords: Neuroanatomia; Morfologia; Morfometria; Vascularização; Encéfalo; Neuroanatomy; Morphology; Morphometry; Vascularization; Encephalon; CIENCIAS AGRARIAS::MEDICINA VETERINARIA